Salted duck egg surface mud removing device - ZHA ANCHUN; LIANG YONG; ZHU WANJING; YIN HENGBING; ZHANG WANLIN; CHEN JING (2025)
The utility model discloses a salted duck egg surface mud removing device, which relates to the technical field of salted duck egg production and comprises a driving motor, a rotating shaft is arranged at the power output end of the driving motor, a circular bottom plate is arranged at the top end of the rotating shaft, and a connecting column is fixedly connected to the middle position of the upper surface of the circular bottom plate. When an operator uses the device to clean the surfaces of the salted duck eggs, water can be injected into the inner walls of the circular rings firstly, then the salted duck eggs are placed in a gap between the two brush plates, and therefore the salted duck eggs can be cleaned conveniently. A power output end of a driving motor rotates to drive a connecting column and a first banister brush on the surface of the connecting column to rotate, a water spraying gun sprays water to the surface of the salted duck egg, and the first banister brush, a second banister brush and a cir